Microplastics in gastric samples from common bottlenose dolphins (Tursiops truncatus) residing in Sarasota Bay FL (USA) - Hart, Leslie B.; Dziobak, Miranda; Wells, Randall S.; Ertel, Bonnie; Weinstein, John (Frontiers in Marine Science, 2022)
The oceans contain trillions of plastic particles, mostly microplastics (i.e., particles < 5 mm diameter; 92.4% of plastic particles), which have been detected in organisms at all levels of the marine food web. The ubiquity of marine plastic debris has created a monumental environmental pollution problem with extensive public health consequences, as more than 40% of the world’s population lives near the coast and shares coastal resources. For decades, common bottlenose dolphins (Tursiops truncatus) have been used as sentinels of marine pollution risks for coastal communities that rely on seafood. Recently, prevalent phthalate exposure was documented in bottlenose dolphins residing in Sarasota Bay, FL, at concentrations exceeding those of human reference populations. While the source of their exposure is uncertain, the types of compounds detected suggest a plastic origin. The objective of this study was to screen for plastic ingestion among free-ranging dolphins in Sarasota Bay using gastric samples collected during catch-and-release health assessments. Gastric samples were collected from seven live bottlenose dolphins in 2019, and suspected microplastic particles were detected in all samples. The number of particles per sample ranged from <10 to >100, and the most common types were transparent films and white foams. Similar to other marine mammal studies, fibers were also present. Given that dolphins are likely exposed to microplastics via contaminated prey, findings from this and additional studies will help to evaluate the potential of contaminated seafood as an additional source of microplastic exposure for humans, as well as help to inform intervention and risk communication needs regarding seafood safety.